Study of the one-neutron transfer reaction in 18O + 76Se collision at 275 MeV in the context of the NUMEN project. (1st March 2023) - Ciraldo, Irene; Cappuzzello, F.; Cavallaro, M.; Carbone, D.; Burrello, S.; Spatafora, A.; Gargano, A.; De Gregorio, G.; Magaña Vsevolodovna, R. I.; Acosta, L.; Agodi, C.; Amador-Valenzuela, P.; et al.
Abstract: Heavy-ion one-nucleon transfer reactions are promising tools to investigate single-particle configurations in nuclear states, with and without the excitation of the core degrees of freedom. An accurate determination of the spectroscopic amplitudes of these configurations is essential for the study of other direct reactions as well as beta-decays. In this context, the 76 Se( 18 O, 17 O) 77 Se one-neutron transfer reaction gives a quantitative access to the relevant single particle orbitals and core polarization transitions built on 76 Se. This is particularly relevant, since it provides data-driven information to constrain nuclear structure models for the 76 Se nucleus. The excitation energy spectrum and the differential cross section angular distributions of this nucleon transfer reaction was measured at 275 MeV incident energy for the first time using the MAGNEX large acceptance magnetic spectrometer. The data are compared with calculations based on distorted wave Born approximation and coupled channel Born approximation adopting spectroscopic amplitudes for the projectile and target overlaps derived by large-scale shell model calculations and interacting boson-fermion model. These reactions are studied in the frame of the NUMEN project. The NUMEN (NUclear Matrix Elements for Neutrinoless double beta decay) project was conceived at the Istituto Nazionale di Fisica Nucleare–Laboratori Nazionali del Sud (INFN-LNS) in Catania, Italy, aiming at accessing information about the nuclear matrix elements (NME) of neutrinoless double beta decay (0 νββ ) through the study of the heavy-ion induced double charge exchange (DCE) reactions on various 0 νββ decay candidate targets. Among these, the 76 Se nucleus is under investigation since it is the daughter nucleus of 76 Ge in the 0 νββ decay process.